Efficiency and benchmarking in the presence of undesirable (bad) outputs: A DEA approach - Jahanshahloo, G.R; Hosseinzadeh Lotfi, F.; Maddahi, R.; Jafari, Y. (International Journal of Applied Mathematical Research, 2012)
Environmental assessment recently becomes a major policy issue in the world. Thisstudy introduces a data envelopment analysis (DEA) model to explore a new use of DEAfor the environmental assessment in which outputs are classified into desirable (good) andundesirable (bad). Such an output separation is important in the DEA-based environmentalassessment. We used a Range-Adjusted Measure (RAM) DEA model for combining thetwo performance measures operational and environmental performance as a unified measure.Reducing the amount of undesirable outputs is the main purpose of environmentalassessment. Therefor, we try to project the inefficient organization on the efficient frontiersuch that the obtained projection produces fewer undesirable outputs than the evaluatedorganization. To reach this goal, it is not important to increase or decrease the amount ofinputs.